Methanol production using carbon capture technology: An overview / Mohd Aizad Ahmad and Zulkifli Abdul Rashid - Ahmad, Mohd Aizad; Abdul Rashid, Zulkifli (Universiti Teknologi MARA Shah Alam, 2018)
Carbon emission to environment cause global warming problems. Research on carbon capture technology has been widely established including pre-combustion, post-combustion and oxyfuel method. Utilisation of carbon from capture process has been developed for methanol production. Various separation method of CO2 from gas has been highlighted. Challenges and potentials of methanol production using carbon capture utilisation (CCU) should be taken into account. The major challenge for methanol production from carbon capture is to produce catalysts which are selective, lower cost and long term recyclable which will allow the reduction of carbon dioxide to methanol. Researchers also discussed how to produce minimum cost of sustainable hydrogen supply to react with CO2. For oxyfuel combustion technology, the challenges are the capital cost and energy consumption mostly from cryogenic air separation unit (ASU). An overview of methanol production using various method of carbon capture has been discussed in this paper.